Tafsir Pluralisme Agama dalam Buku Fiqih Lintas Agama Kajian dan Kritik - Achmad Yaman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
This study aims to demonstrate the existence of irregularities or irregularities in the interpretation of the Qur'an by the authors, particularly matters of a sensitive nature and principles of the Islamic Shariah. This research method using comparative studies critique of the authors in explaining the interpretation of Religious Pluralism. The authors used a new approach according to their interpretation, known as hermeneutics method, a method that is both contextual and interpret anything, including the Koran in a way that liberal, free gratuitous even impressed with not maintaining the sanctity of the holy book of the Muslims. Based on the research results, it can be concluded that the interpretation of the authors of Religious Pluralism using hermeneutic approach does not fit with the mainstream of Islamic teachings or methodology interpretations by scholars who no doubt their knowledge and understanding of the Koran.